The Android-Based Visual Audio in Training Single Category Pencak Silat Motion - Alfarizi, Muhammad Rizky; Sulaiman, Sulaiman; Rustiadi, Tri (Journal of Physical Education and Sports, 2020)
The modern technology used in international martial arts is virtual reality, while the martial arts technology used in Indonesia is a guidebook, motion capture, video, VCD containing audio visuals, and video tutorials. The purpose of this study is to develop an Android-based audio-visual media in a single category martial arts exercise, testing product acceptance, and the effectiveness of the products produced. This research is a research and development conducted with ten stages of research and development from Borg and Gall. The stages of research undertaken are (1) literature review, (2) initial draft, (3) expert validation, (4) revision 1, (5) product 1, (6) small-scale trial, (7) revision 2, ( 8) product 2, (9) large-scale trial, (10) final product. The results of the research and development is a single-category android-based audio visual media motion pencak silat media product. The product has been validated by material experts and media experts with very good results (92.00%) and (89.17%), small-scale trials that were tested on trainers, judges and athletes of the Merpati Putih Pencak Silat UKM UKM Tidar Magelang State University with very good results (92.05%). Large-scale trials were conducted at PAMUR Magelang District Magelang and obtained very good results (88.75%). Operational tests were conducted at PAMUR colleges with the results of a significant increase in the test items (0.001 <0.05) and single category demonstrations (0.024 <0.05). The conclusions of the results of research and development of audio-visual media in the category of single-motion martial arts based on android is feasible and effective to be used for supporting media for the exercise of single-category martial arts. Suggestions for athletes, coaches and judges that this media can be used to support the training process.